2019
DOI: 10.3390/su11061569
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency as a Wicked Problem

Abstract: Together with increased shares of renewable energy supply, improved energy efficiency is the foremost means of mitigating climate change. However, the energy efficiency potential is far from being realized, which is commonly explained by the existence of various barriers to energy efficiency. Initially mentioned by Churchman, the term "wicked problems" became established in the 1970s, meaning a kind of problem that has a resistance to resolution because of incomplete, contradictory, or changing requirements. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Energy efficiency is termed as "a wicked problem" due to the ambiguity of the problem itself. The meaning varies depending on the societal sector, modeling, and the research community [67]. In Reference [38], the authors indicated that, despite the proposal for effective technical policy approaches, the government introduced several neoclassical perspectives on the policy involving improvements on other mechanisms that are not rigorously connected to the energy efficiency plan.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Energy efficiency is termed as "a wicked problem" due to the ambiguity of the problem itself. The meaning varies depending on the societal sector, modeling, and the research community [67]. In Reference [38], the authors indicated that, despite the proposal for effective technical policy approaches, the government introduced several neoclassical perspectives on the policy involving improvements on other mechanisms that are not rigorously connected to the energy efficiency plan.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The role of energy planning, apart from the technical sphere, needs to include perspectives from social-economic and environmental spheres to align with the sustainable development agenda. The complex interactions in these three spheres, different stakeholders involved in planning, and difficulty in defining it makes it a 'wicked problem' (Cajot et al, 2015(Cajot et al, ,2017Thollander et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Wicked problems are complex problems, which usually involve multiple stakeholders with their own worldviews, leading to variable definitions of the problem, which can sometimes be contradictory (Cajot et al, 2015;Garcia et al, 2016;Thollander et al, 2019). Such problems show resistance to resolution because of incomplete, contradictory, and changing requirements (Coulton et al, 2014;Thollander et al, 2019). Due to the uncertainty and ambiguity that wicked problems involve, technical analysis is unlikely to provide a final resolution (Thollander et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability challenges are often labeled as wicked problems [1,2], ranging from climate change [3], to energy transitions [4] and urban development [5]. Wicked problems have the following characteristics.…”
Section: Introductionmentioning
confidence: 99%